2005
DOI: 10.1097/01.wnr.0000175247.35837.15
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral hemodynamic responses to auditory stimulation in newborn infants

Abstract: We studied hemodynamic auditory evoked responses of 20 healthy full-term neonates with near-infrared spectroscopy. The instrument used allows the measurements to be performed simultaneously above both auditory cortices. The stimulation consisted of 5-s trains of sound (700-ms interstimulus interval) with a 25-s silent interval. In response to the stimulation, a significant increase in concentration of oxygenated hemoglobin was detected in 14 out of 21 measurements. The mean latency of the largest response was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 16 publications
4
33
0
Order By: Relevance
“…However, they provide less equivalent temporal information unless multiple frequencies are employed, and operate less efficiently at very low intensities (Nissilä et al, 2006). Optical topography systems have been built based on both time-domain (Quaresima et al, 2005) and frequency-domain (Danen et al, 1998;Choi et al, 2004;Kotilahti et al, 2005) technologies. Their disadvantage compared to CW systems is their comparatively high cost, and slower sampling rates (particularly for photon-counting systems).…”
Section: Time-domain and Frequency-domain Spectroscopymentioning
confidence: 99%
“…However, they provide less equivalent temporal information unless multiple frequencies are employed, and operate less efficiently at very low intensities (Nissilä et al, 2006). Optical topography systems have been built based on both time-domain (Quaresima et al, 2005) and frequency-domain (Danen et al, 1998;Choi et al, 2004;Kotilahti et al, 2005) technologies. Their disadvantage compared to CW systems is their comparatively high cost, and slower sampling rates (particularly for photon-counting systems).…”
Section: Time-domain and Frequency-domain Spectroscopymentioning
confidence: 99%
“…14 NIRS studies with auditory cortex activation have been also reported for both adults [27][28][29] and infants. 30,31 These studies are mainly based on linguistic viewpoint. On the other hand, this study focuses on simple auditory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, NIRS has the great advantage of enabling investigation of stimulusinduced cortical activation in relation to perceptual and cognitive activity in awake infants [13,25,[53][54][55][56][57][58][59]60,61]. Regarding the development of auditory and language perception, NIRS measurements have been performed during sleep [14,[62][63][64][65][66][67]. Most of these studies have examined whether the cortical regions of interest in infants of different ages selected using behavioural studies showed hypothesized responses based on adult neuroimaging studies.…”
Section: (D) Developmental Changes In Stimulus-induced Activitymentioning
confidence: 99%